A facile and cheaper method to measure root angle of rice and wheat - SAKHARE, AKSHAY S; KUMAR, SUDHIR; KUMAR, RANJEET RANJAN; BAINSLA, NARESH KUMAR; GAIKWAD, KIRAN; SHARMA, R K; CHINNUSAMY, VISWANATHAN (The Indian Journal of Agricultural Sciences, 2019)
Genetic improvement in root system architecture (RSA) is an important trait to achieve stability of grain yield in water-deficit stress environments. Deep rooting is a major component trait that contributes to dehydration avoidance under drought in most crops. Due to the difficulty in the phenotyping for deep rooting, genetic variability in deep rooting is less exploited in genetic improvement programme. Root angle is a surrogate for deep rooting. Here, we report a novel method to measure root angle which is easy, robust and cheaper. By using this method, 56 wheat and 29 rice genotypes were phenotyped for root angle under field conditions. Wide variability in root angle was observed among rice and wheat genotypes. In rice, about 58% of crown roots were having shallow angle (60Â°). This method could categorize the previously known shallow rooted rice cv. IR6 4 in to shallow root category with >90% of its crown root with an angle of 60% of crown roots with >60Â° and identified as deep-rooted genotype. In wheat CL 3791, CL 3817 and CL 3823 were identified as deep-rooted genotypes. This method issuitable for high throughput phenotyping of root angle in natural field conditions.